Quality Management in Indonesia Maritime Education: Is it well implemented? - Sarinten Sarinten; Pujaningsih Pujaningsih; Badiatul Islami; Mahardhika Andiansyah (Journal of Innovation in Educational and Cultural Research, 2022)
The adoption of Total Quality Management (TQM) in educational institutions has not been thoroughly optimized, resulting in a wide range of results. This study aims to determine the key features of TQM used by maritime education and training institutes in Indonesia and the results. This study used descriptive quantitative methodologies using eleven institutions, the most extensively used TQM elements as measuring variables, and the findings. The respondents are 16 members of the institution's quality management team. Strategic quality planning (5.99), information and analysis (5.90), involvement of teaching staff and employees (5.86), knowledge and training (5.80), leadership and top management commitment (5.76), and process management were found to be the most often used TQM elements (5.76). Meanwhile, the most significant results of TQM implementation in the sample institutions were improving operational performance (6.06), teaching staff and employee satisfaction (5.90), and customer satisfaction (5.79). This study adds to the empirical literature on TQM in Indonesian maritime educational institutions by identifying the most often used TQM elements and the result achieved.